Promoting peer acceptance in the classroom: an evaluation of a cooperative learning intervention in a mainstream primary school - Craig, Jonathan (2010)
This study evaluates the effectiveness of a Cooperative Learning intervention upon the mean peer acceptance levels of all children (N=54) within two Year four classes in a mainstream primary school in the North West of England.